2017
DOI: 10.3389/fimmu.2017.00704
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of MicroRNAs in Probiotics-Induced Reduction of the Cecal Inflammation by Salmonella Typhimurium

Abstract: The microRNAs (miRNAs) have been shown to play important roles in the development of the immune system and in regulation of host inflammation responses. Probiotics can effectively alleviate the inflammation caused by Salmonella in chickens. However, whether and how miRNAs are involved in modulation of the inflammation response in the gut of chickens have not been reported. In this study, the impact of a probiotics, Lactobacillus plantarum Z01 (LPZ01), was investigated on the cecal miRNAs and cytokine secretion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 49 publications
0
34
0
Order By: Relevance
“… 22 In addition, Lactobacillus can affect the expression level of certain cytokines and miRNAs such as miR-375, miR-122-5p, miR-193a-5p, and miR-3525, as well as miR-215-5p in chickens infected by Salmonella Typhimurium. 23 In addition, Lactobacillus was shown to be present in the fecal samples collected from healthy centenarians and was used to alleviate the severity of food induced allergies in mice by promoting the production of transforming growth factor β (TGF-β) in regulatory T cells (T-regs). 24 Furthermore, the administration of an oral dose of Lactobacillus in rats could alleviate the symptoms of AHR and reduce the severity of inflammations in the airways, as well as reduce the response of IL-17 induced by the exposure to PM2.5 and OVA.…”
Section: Discussionmentioning
confidence: 99%
“… 22 In addition, Lactobacillus can affect the expression level of certain cytokines and miRNAs such as miR-375, miR-122-5p, miR-193a-5p, and miR-3525, as well as miR-215-5p in chickens infected by Salmonella Typhimurium. 23 In addition, Lactobacillus was shown to be present in the fecal samples collected from healthy centenarians and was used to alleviate the severity of food induced allergies in mice by promoting the production of transforming growth factor β (TGF-β) in regulatory T cells (T-regs). 24 Furthermore, the administration of an oral dose of Lactobacillus in rats could alleviate the symptoms of AHR and reduce the severity of inflammations in the airways, as well as reduce the response of IL-17 induced by the exposure to PM2.5 and OVA.…”
Section: Discussionmentioning
confidence: 99%
“…In the miRBase database, miR-3525 is unique among chickens. Previous studies on gga-miR-3525 focused on lung, trachea [12], and cecum [13]. To the best of our knowledge, this is the first study to examine its role in skeletal muscle development.…”
Section: Discussionmentioning
confidence: 91%
“…gga-miR-3525 (miRBase accession number: MIMAT0016382) is specifically expressed in chickens [11]; it was first identified in the lungs and trachea of chickens infected with avian influenza virus and found to target the interleukin-6 signal converter (IL6ST) [12]. Chen et al found that gga-miR-3525 was involved in probiotics-induced reduction of cecal inflammation by Salmonella Typhimurium in neonatal broiler chickens [13]. Additionally, expression of gga-miR-3525 is altered after heat stress in layers, suggesting that gga-miR-3525 may participate in regulation of heat stress-induced damage in the chicken [14].…”
Section: Introductionmentioning
confidence: 99%
“…It is a major food-borne pathogen and has an impact on the microbiological safety of eggs which is also a risk factor to humans [165]. A previous study revealed 14 miRNAs that were significantly altered by the infection of S. typhimurium [166]. Among them, miR-3525, miR-215-5p, miR-193a-5p, miR-122-5p, and miR-375 were verified by qRT-PCR.…”
Section: Ncrnas and Salmonella Typhimuriummentioning
confidence: 91%
“…Among them, miR-3525, miR-215-5p, miR-193a-5p, miR-122-5p, and miR-375 were verified by qRT-PCR. The predicted DEmiRNAs target genes were enriched in immune system development, stress-activated MAPK cascade, the regulation of cAMP-dependent protein kinase activity, and the regulation of immune system process (such as, MAPK and Wnt signaling pathways) [166].…”
Section: Ncrnas and Salmonella Typhimuriummentioning
confidence: 99%